Studying the biodiversity and abundance of the red marine algae Rhodophyta in Jableh beach and identifying promising species for economic investment. - عراج, هديل (Latakia University Journal -Biological Sciences Series, 2022)
Sixty-two species of red algae were recorded at Mina El-Rus, due to the diversity of its coastal ecological habitats, in addition to the presence of the Al-Rus River, which carries nutrients. It was observed that there are 5 species in the M1 station, which is a small number compared to the M2 station (13 species) and the M3 station (28 species). The abundance of most species was seasonal, either in the spring or in the fall, and the emergence of some species was limited to the spring season to provide the appropriate conditions of heat and nutrients. The crustacean species dominated in the middle coastal layer, then the large species dominated in the lower coastal layer, allowing the field for vegetative application. The environment has become more suitable for them, such as the relative increase in water temperature. Seven species of economically investable red marine algae have been identified in terms of importance and abundance.